West Palaearctic species belonging to the subgenus Orthocladius s. str. (Diptera, Chironomidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A list of the species belonging to the subgenus Orthocladius s. str.van der Wulp, 187 4 known to occur in the West Palaearctic is here reported. Recentchanges in nomenclature are described. Only species well known both as adultmales and pupae are considered.
Keywords: Orthocladius s. str.; Chironornidae; Diptera Nematocera